Competing Grounds of Hadith Authority in the Thought of Kassim Ahmad and M. Syuhudi Ismail in Late-Twentieth-Century Malaysia and Indonesia - Abbas Langaji; Nur Laili Nabilah Nazahah Najiyah; Saifuddin Zuhri Qudsy (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2026)
Modern debates about hadith are often organized through the binary of rejection and defense. That classification identifies polemical positions but obscures the different standards by which prophetic reports are made religiously binding. This article compares Kassim Ahmad and M. Syuhudi Ismail as two parallel, asymmetrical projects in late twentieth century Malaysia and Indonesia. Using qualitative document analysis, contextual close reading, directed content analysis, and structured-focused comparison, it examines seven primary works through five dimensions: foundational norm, status of hadith, validation procedure, authorized mediator, and normative reach. The analysis finds that Kassim does not deny the possible historical existence of reports about the Prophet; he subordinates their authority to Qur’anic, historical, and rational adjudication and treats them as defeasible historical precedents. Syuhudi, by contrast, preserves hadith as a normative source while conditioning its acceptance and application on disciplined sanad-matn criticism, identification of the Prophet's function, and contextual interpretation. Both projects reject unexamined reception, but they assign final jurisdiction to different procedures and forms of competence. The comparison therefore reframes modern hadith controversy as a contest over how authority is organized rather than a simple conflict between tradition and reason.